A Rare Quadruple Association: Fibromuscular Dysplasia, Giant Splenic Artery Aneurysm, Extrahepatic Portal Hypertension, and Hypersplenism - Shinde, Sweety (Indian J Crit Care Med, 2021)
Fibromuscular dysplasia (FMD) is a non-atherosclerotic, non-inflammatory vascular lesion. It is a very rare cause of splenic artery aneurysm (SAA). An 18-year-old girl presented with hematemesis, melena, pancytopenia, and splenomegaly. Endoscopy showed esophageal varices. Computed tomography angiography showed splenic infarct and a giant splenic artery aneurysm. Portal vein showed cavernous transformation with enlarged periportal and lienorenal collaterals. The liver and pancreas were unremarkable. Microscopy of the SAA revealed intimal fibroplasia and medial dysplasia. Symptoms of extrahepatic portal hypertension were relieved by aneurysmectomy, thus proving SAA as the underlying cause. Pancytopenia was reversed post-splenectomy, thus proving hypersplenism. This is the first-ever report showing a quadruple association of FMD, splenic artery aneurysm, extrahepatic portal hypertension, and hypersplenism. KEY MESSAGES: Fibromuscular dysplasia can present as a giant aneurysm of the splenic artery. The resultant extrahepatic portal hypertension and splenomegaly can result in hypersplenism. Splenectomy and aneurysmectomy can reverse pancytopenia and portal hypertension. HOW TO CITE THIS ARTICLE: Shinde S. A Rare Quadruple Association: Fibromuscular Dysplasia, Giant Splenic Artery Aneurysm, Extrahepatic Portal Hypertension, and Hypersplenism. Indian J Crit Care Med 2021;25(1):100–103.